Re-evaluation of the Wehrle’s salamander (Plethodon wehrlei Fowler and Dunn) species group (Caudata: Plethodontidae) using genomic data, with the description of a new species - Felix, Zachary I.; Wooten, Jessica A.; Pierson, Todd W.; Camp, Carlos D. (Zootaxa, 2019)
Woodland salamanders of the genus Plethodon are characterized by strong ecological and morphological conservatism. One assemblage, the Wehrle’s salamander (Plethodon wehrlei Fowler & Dunn) species group, is distributed from New York to Tennessee, USA, and includes several morphological variants, four of which are sufficiently distinct to have been recognized as species in the past. For many years after two of these species were placed in synonymy, only P. wehrlei and P. punctatus Highton were recognized. A recent phylogeographic study using mitochondrial DNA and nuclear DNA uncovered considerable genetic diversity within the group and conservatively resurrected one of the previously synonymized forms (P. dixi Pope & Fowler). However, their analysis could not resolve all relationships among remaining populations of P. wehrlei, leaving the taxon paraphyletic. We re-evaluated the evolutionary history of this group using genomic data, recovered strong support for at least five distinct clades, and corroborated previously reported relationships. We also collected morphological data and demonstrated morphological distinctiveness for four of the five clades that we herein recognize as species. We resurrect the synonymized name P. jacksoni Newman to represent the southern clades of P. wehrlei in southwestern Virginia and North Carolina exclusive of P. dixi. In addition, we describe a yellow-spotted form of P. wehrlei endemic to the Cumberland Plateau as a new species. Although our proposed changes rectify the paraphyly of P. wehrlei, our sampling was not sufficient to resolve potential taxonomic issues remaining within the species herein recognized as P. jacksoni.